Totobaggu by SofeaKamilia / Aisya Sofea Zainul Ekhwan and Kamilia Komaruddin - Zainul Ekhwan, Aisya Sofea; Komaruddin, Kamilia (2022)
Totobaggu by SofeaKamilia was established with the goal of offering affordable, stylish, and unique tote bags to our target market that consists of young adults aged from 15 years old to 30 years old. Totobaggu’s main purpose is so that everyone can own a tote bag that not only allows them to carry their desired things but can also be a fashion accessory. Totobaggu is still relatively new in the market when compared to other brands, but with its newly released collection, The Elements and Citrus, the brand managed to capture the attention of locals. Aisya Sofea and business partner Kamilia launched the brand in May 2022. They both decided to use the name Totobaggu, which was suggested by the founder, Aisya, and subsequently accepted to use by Kamilia for their tote bag business. Totobaggu is a Japanese term that means "tote bag." Orange and purple, which are the theme colours for the business, are used to showcase the bright, fun and youthful concept of Totobaggu’s tote bags that are deeply influenced by the Japanese fashion scene. To add significance to the name, they decided to merge both of their names to demonstrate the uniqueness and collaboration of the business's key personnel in developing Totobaggu in the market. This online based business, uses social media to advertise its products and engage with customers via Facebook and Whatsapp. Totobaggu by SofeaKamillia has a shipping system, where we deliver the orders received twice a week, on Tuesday and Friday using local couriers. This way, our clients are ensured to receive their tote bags on time. Thus far, they have released two tote bag designs, Elements and Citrus. The brand's current collection has been a big success, with one of their products selling out within a week of release.